Pharmacotherapy for Retinoblastoma - Shahsavari, Mohsen (Ophthalmic Research Center, 2009)
Systemic chemotherapy has become the cornerstone of therapy for retinoblastoma. The advent of novel chemotherapeutic and antiangiogenesis agents together with new routes of drug administration including periocular, intravitreal and intra-ophthalmic artery injection will hopefully revolutionize the management of this sight-threatening and potentially fatal infantile ocular neoplasm.